A stereoregular macrocyclic oligomeric silsesquioxane bearing epoxide groups: synthesis and its nanocomposites with polybenzoxazine. Issue 94 (14th October 2015) - Wei, Kun; Liu, Ning; Li, Lei; Zheng, Sixun
<x xml:space="preserve">Abstract</x> cis-Hexa(phenyl glycidyl) MOSS, a novel macrocyclic oligomeric silsesquioxane (MOSS) was synthesized and incorporated into polybenzoxazine to obtain the organic–inorganic nanocomposites.